Pre-operative sarcopenia as reflected by computed tomography predicts post-operative complications in patients undergoing total laryngectomy for head and neck cancer : a systematic review and meta-analysis - Le, Khang Duy Ricky; Sharp, Samuel; Cheong, Edward; Vuong, Karen; Greiff, Lennart; Carlwig, Kristin (Australian Journal of Otolaryngology, 2025)
Background: Head and neck cancer patients often experience muscle wasting due to malnutrition and the hypermetabolism of cancer. For those undergoing total laryngectomy (TL), there is the potential for peri-operative complications. Sarcopenia has gained recognition as a prognostic factor in head and neck cancer. However, there is marked variability in the ways sarcopenia is defined and poor characterisation of its effect in patients undergoing TL. This review evaluates the role of sarcopenia as reflected by computed tomography (CT) on the post-operative outcomes for patients undergoing TL. Methods: A literature search was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies evaluating sarcopenic versus non-sarcopenic patients as reflected by CT imaging on post-operative and oncological outcomes following TL were eligible. Results: Four studies encompassing 475 patients were included. There was evidence that sarcopenia as reflected by CT is a prognostic indicator of total post-operative complications [odds ratios (OR) 2.29, 95% confidence interval (CI): 1.05–4.97, P=0.04] and pharyngocutaneous fistula (PCF) development (OR 2.28, 95% CI: 1.45–3.59, P=0.0004) following TL for cancer. This is based on a foundation of studies at moderate risk of bias. Conclusions: Sarcopenia is a significant prognostic marker for post-operative complications and PCF formation in cancer patients undergoing TL. This finding is based on single-institution observational evidence with high clinical heterogeneity and poor control for confounders. Larger prospective clinical trials are required to further characterise the impact of sarcopenia on outcomes following TL.
Publisher Copyright: © AME Publishing Company, Australian Society of Otolaryngology Head & Neck Surgery.
Keywords: computed tomography (CT); laryngeal cancer; laryngectomy; post-operative complications; Sarcopenia